Strategi Pemerintah Daerah Provinsi Jawa Timur Dalam Mewujudkan Program Jatim Bangkit (Riset Deskriptif Kualitatif pada Kampanye Jatim Bangkit)19 - Ufliasari, Rizka (Universitas Dr. Soetomo Surabaya, 2023)
All sectors, from micro, medium and small enterprises (MSMEs) to the tourism industry have been affected by the COVID-19 outbreak. Creating micro-scale policies that promote rapid local economic recovery is the primary responsibility of local governments. East Java to continue to be aware of potential threats from the impact of the COVID-19 pandemic, even though the province is described as having good financial system stability in the fourth quarter of October-December 2020. Khofifah Indar Parawansa understands this problem by realizing the